2022
DOI: 10.1109/access.2022.3159651
|View full text |Cite
|
Sign up to set email alerts
|

A Taxonomy of Fake News Classification Techniques: Survey and Implementation Aspects

Abstract: In the present era, social media platforms such as Facebook, WhatsApp, Twitter, and Telegram are significant sources of information distribution, and people believe it without knowing their origin and genuineness. Social media has fascinated people worldwide in spreading fake news due to its easy availability, cost-effectiveness, and ease of information sharing. Fake news can be generated to mislead the community for personal or commercial gains. It can also be used for other personal benefits such as defaming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 104 publications
0
11
0
1
Order By: Relevance
“…LSTM achieved an average accuracy of 94.21%. Similarly, Rohera et al [12] also shows LSTM outperform SVM, random forests (RF), and SVM in classifying fake news. On the other side, [13] found that XGBoost (XGB) and RF performed best in detecting fake news among k-nearest neighbors (KNN), NB, RF, SVM with RBF kernel (SVM), and XGB.…”
Section: Introductionmentioning
confidence: 90%
“…LSTM achieved an average accuracy of 94.21%. Similarly, Rohera et al [12] also shows LSTM outperform SVM, random forests (RF), and SVM in classifying fake news. On the other side, [13] found that XGBoost (XGB) and RF performed best in detecting fake news among k-nearest neighbors (KNN), NB, RF, SVM with RBF kernel (SVM), and XGB.…”
Section: Introductionmentioning
confidence: 90%
“…72 [123] A Taxonomy of Fake News Classification Techniques: Survey and Implementation Aspects 73 [124] The Impact of the COVID- [134] Public perception of SARS-CoV-2 vaccinations on social media: Questionnaire and sentiment analysis 84 [135] Identifying Covid-19 misinformation tweets and learning their spatio-temporal topic dynamics using Nonnegative Coupled Matrix Tensor Factorization 85 [136] Cultural Evolution and Digital Media: Diffusion of Fake News About COVID-19 on Twitter 86 [137] Covid-19 vaccine hesitancy on social media: Building a public twitter data set of antivaccine content, vaccine misinformation, and conspiracies 87 [138] News media stories about cancer on Facebook: How does story framing influence response framing, tone and attributions of responsibility?…”
Section: [72]mentioning
confidence: 99%
“…Classification involves grouping entities based on a set of ordered features. In this work, 3D convolutional neural networks (3D CNNs) [ 50 , 51 , 52 ] were employed to classify tumors into LGG and HGG categories. The 3D CNNs have successive convolution layers and rectified linear unit (ReLU) functions.…”
Section: The Proposed Etistp Modelmentioning
confidence: 99%